Augmenting diagnostic vision with AI - Quer, Giorgio; Muse, Evan D; Nikzad, Nima; Topol, Eric J; Steinhubl, Steven R (The Lancet (British edition), 2017)
Computer-aided diagnostics are nothing new in medicine. What is different now is that with deep learning, a class of machine learning algorithms, the system autonomously learns and improves.